Analysis of the Effect of Variations in Organic Waste Composition on Body Weight Growth of Black Soldier Fly Larvae (Hermetia Illucens) - Auliani, Restu; Apsari, Desy Ari; Rusli, Mustar (GLOBAL HEALTH SCIENCE GROUP, 2024)
The increasing amount of organic waste requires special attention in its management. Efforts to conserve and manage organic waste in bioenergy are one of the current intensive efforts through the cultivation of BSF maggots. This study aims to see the effect of variations in waste composition on body weight growth in maggot growth, analyze fat, protein, and water content based on variations in waste composition decomposed by maggot, and determine the Waste Reduction Index (WRI). This research is a quasi-experiment with the pre-and-post Group Design method, using 5 variations of a waste composition consisting of catering waste, vegetable and fruit waste with washing or chopping treatment. The growth of magot larvae body weight was best in the variation of catering waste with slurry treatment, with the final weight of magot reaching 3025 grams from the initial weight of larvae weighing 50 grams. Proximate analysis was carried out on a maggot that was 21 days old, namely water content ranging from 60.73% to 65.42%, and fat content from 47.29% - 51.24%. The protein content is 19.11% - 42.76%. The results of one-way Anova analysis obtained Sig value. (0.000) < α then H0 is rejected, it can be concluded that the five variations of waste composition in maggot feed have a different average weight gain of maggot, and have different weight gain. The WRI value obtained is 2.4 - 2.99.